Sistem Otomatisasi Desalinasi Air Laut Berbasis Internet of Things - Deni Maulana Ihsan; Novi Prihatiningrum; Limawati Handayani; Faisal Budiman (Akademi Angkatan Udara, 2021)
The design of automatic sea water desalination device based on Internet of Things (IoT)utilizing the thermal desalination method has been carried out. Thermal desalination is a process of salt water into pure water vapor conversion, thus the salt, minerals, and other contaminants that present in the water will be separated. The system is useful to convert sea water into fresh water, which is beneficial for community that living at coast area. The designed thermal desalination device consists of temperature, salinity, and ultrasonic sensors, which are connected to a microcontroller. In addition, the device is also equipped with an IoT system and a mobile application, for controlling and monitoring features through an android application. When the application in operation, the temperature, volume, and salinity levels data are sent via the IoT platform, so that it can be monitored by the users through an android application in mobile phone. The experimental results showed that this desalination device has succeeded in converting salt water into freshwater, with a percentage of freshwater volume after desalination process reaching 92.74%. For each process, the duration requires about 3 h. The design results, testing, mechanism, and discussion in more detail are presented in this article.